Cyanide-free copper electrodeposition using glycerol: Modeling and optimization - Lima, Lucas Franklin de; Azevedo, Ila Gabriele Diniz Dias de; Magalhães, Karen Giovanna Duarte; Pereira, André Anderson Costa; Souza, Carlson Pereira de; Melo, Raffael Andrade Costa de (Brazilian Journal of Production Engineering, 2025)
The electrodeposition of copper on a Cu-Zn alloy substrate (brass) is normally carried out using alkaline hydrocyanic baths. However, cyanide copper baths are toxic and require certain care. This work studies the modeling and optimization of copper electrodeposition on brass using an electrolytic bath containing cyanide-free glycerol. A central composite experimental design was carried out to evaluate the effects of the factor’s glycerol concentration, time and amperage in response to cathodic current efficiency. The results showed that the estimated model is predictive (R² equal to 0.9279), with the effects of the linear and quadratic terms of amperage, linear terms of glycerol concentration and the effects of their interactions being significant. The best test resulted in a cathodic current efficiency of 57% and an energy consumption of 234.40 kWh/kg, which represented the highest copper deposition and the lowest energy consumption.
Keywords: Copper electrodeposition; optimization; electrolytic bath; glycerol; experimental design